PEMBUATAN PEMBANGKIT LISTRIK TENAGA MIKROHIDRO TURBIN ULIR SKALA LABORATORIUM - Esron Robet Lubis (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2022)
River flow is one of the renewable energy sources that can be used for micro hydro power plant "screw Archimedes". Archimedes screw turbine design and manufacture is being developed for micro hydro power generation. Archimedes screw turbines can be operated at low heads. In Indonesia, especially the province of North Sumatra, it has great potential considering the large number of streams in the mountains or hills so that the surrounding community will later be able to take advantage of the relatively small currents of the existing rivers, when applied to river flows that have a relative height of 0.5 meters to 1 meter even though on the water that flows a little wavy, the screw turbine can of course be used, that is the advantage of the PLTMH tool. The geometry of the screw turbine is determined by external parameters, namely the outer radius, turbine length and laying slope and internal parameters, namely the radius in the number of blades.External parameters are usually determined by head and discharge. The purpose of this research is the manufacture of a laboratory-scale screw turbine micro-hydro power plant, producing a screw turbine installation for experimental studies of laboratory-scale micro-hydro power plants. Furthermore, this installation will be used for tests on external parameters and internal parameters of the Archimedes screw turbine. The result of the design and manufacture of a screw turbine on a laboratory scale is a screw turbine model made using angled iron material and an iron plate with a geometric shape of two blades, the number of turns is 6, the turbine length is 870 mm with a blade distance of 290 mm.